Comparative Overview on Word-Compounding in English and Albanian - Sherko, Esmeralda (Mediterranean Journal of Social Sciences, 2012)
This paper presents a comparative bilingual overview, by comparing word formation in two languages, respectively Albanianand English, as well as the main word formation trends in both languages. Both languages display a variety of word formationtechniques, but their classifications according to different ways are not in complete conformity with each other. An example of this isâ€œpÃ«ngjitjaâ€1, which in Albanian is classified as an independent class form the compound nouns, while in English it appears under theheading of â€œcompoundsâ€. The paper will also highlight spelling and phonetic differences in both languages. In Albanian language theâ€œpÃ«rngjitjaâ€ is formed by the monomial of word group or phrase, a prepositional phrase or a group of words in general. The syntacticrelations between the terms of the phrase or the group are usually preserved clearly, even in the structure of the newly formed word -tÃ«pÃ«rngjitur. In English compounding, which also includes pÃ«rngjitja refers to the process of combining two words to form a new one,where the words added at the beginning to a certain extent subcategorizes the words following it.